Navigating the Contemporary Rites of Passage: A Typology of STEM Professional Identity Transition - Yit Sean Chong; Ai Hwa Quek (Research in Social Sciences and Technology, 2022)
Anchored upon a renewed rites of passage perspective, this study employs a narrative inquiry to understand how professional identities are enacted, developed, negotiated, and reconstructed among final year STEM undergraduates in Malaysia. While professional identities are largely studied within the workplace or organisational context, there is limited knowledge of how students make sense of their professional identities during their study. To address this gap, this study explores the dilemmas and dreams of twenty-four final year STEM undergraduates as they were at the critical juncture of transition towards their first full-time career. While the participants shared a common experience of STEM professional identity formation during their childhood and adolescent phases of life, there were variations in how individuals negotiated their professional identities as they reached the crossroads upon university enrolment and graduation. In navigating the liminal phase of uncertainties, negotiation strategies included defending and rethinking STEM professional identities while balancing identities in work and non-work roles. Towards the reconstruction phase, a process of redefining, affirming, and securing STEM professional identity takes place as individuals make sense of their roles and place in the communities. The narrative findings illustrate contemporary dynamics of societal expectations, structural forces and personal agency that facilitate STEM professional transitions. The study also adds insights into emerging discourses surrounding STEM education and talent retention strategies among the contemporary STEM workforce.